Speech on Welcoming H.E. Mr. Takeo Fukuda - Ungku Abdul Aziz, Ungku Abdul Hamid (1982)
Ungku's speech on welcoming H.E. Mr. Takeo Fukuda. The draft speeches are available in both English and Japanese version.